Comparison of the diversity and biomass of beach-cast seaweeds from NE and SE Brazil. Issue 3 (3rd July 2022) - Leal Gondim Cavalcanti, Maria Irisvalda; González Sánchez, Patricia María; Fujii, Mutue Toyota
ABSTRACT: Stranded seaweeds are reported worldwide; along the Brazilian coast, the occurrence of beach-cast seaweeds is increasing. In this study the diversity, coverage and biomass of beach-cast seaweeds were compared on the north-eastern (NE) and south-eastern (SE) coasts of Brazil. In total 110 taxa were identified: 80 Rhodophyceae, 13 Phaeophyceae and 17 Chlorophyceae. While the NE coast had higher species richness, the SE beaches exhibited higher coverage and biomass, predominantly Phaeophytes within the Dictyotales. The identified taxa were attributed to five functional-form groups and their respective frequencies were calculated and analysed. In Brazil, corticated species displayed the highest frequency at all study sites, especially Emboaca Beach, whereas the corticated foliose group was more frequent on Candeias, Itaoca and Pontal Beaches. A permutational analysis of variance revealed significant differences in coverage and biomass of the macroalgal assemblages across beaches. A homogeneity of multivariate dispersions indicated that these parameters also differed significantly between the NE and SE coasts, with a marked dissimilarity between the beaches studied. Our results will contribute to a better understanding of the biodiversity and biomass of beach-cast seaweeds for possible future economic use (e.g. as fertilizer) in a region where local incomes are low.